Ivan Lypa – student of the School of Medicine, Kharkiv University - Glybytska, Svitlana (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Purpose: is to clarify the years of Ivan Lypa’s study at the Medical Faculty of Kharkiv University, to find out which of the famous doctors taught during his studies, how the educational process at the Medical Faculty of that time went, to study the public activities of Ivan Lypa during his student years. Research methodology is based on the principles of historicism, objectivity and systematicity. Scientific novelty. Based on university sources, the year of Ivan Lypa’s admission to the Medical Faculty of Kharkiv University was specified; it was found out which of the famous doctors taught during I. Lypa’s studies at the university, how the lectures were held, in particular on surgery, how practical classes were held in various clinics of the university, how the fight against the cholera epidemic, in which Ivan Lypa took part, was carried out; the Kharkiv period of activity of the founder of the Ukrainian secret society ‘Brotherhood of Tarasivtsi’ was studied. Conclusions. Ivan Lypa’s student years in Kharkiv were very important in his development as a doctor and public figure. Studying under talented medical professionals who taught at the Kharkiv university, he acquired the diverse knowledge and skills that formed the basis of his professional career. As a student, Ivan Lypa became one of the founders of the Ukrainian secret organisation Brotherhood of Tarasivtsi, went through the ordeal of prison and developed into a true fighter for the freedom of the Ukrainian people.